Ultrastructural changes in chronic inflammatory enteropathies—a comparison between dogs and humans - Fietz, Simone A.; Kalusa, Mirjam; Jergens, Albert E.; Sahoo, Dipak Kumar; Stewart, Tracey; Heilmann, Romy M. (Frontiers in Cell and Developmental Biology, 2024)
Chronic inflammatory enteropathies (CIE) are an important group of diseases in dogs and involve complex pathogeneLc aspects. Endoscopy and histopathology are vital to document the disease but are less useful to subclassify CIE and predict the response to treatment. However, healing of the mucosal disease process (deep remission) and ultrastructural evaluaLon of the mucosa have received lible abenLon in canine CIE. Given that canine CIE shares many similariLes with inflammatory bowel diseases (IBD) in human paLents -and presents a good spontaneous disease model for human IBD -this perspecLve arLcle evaluates the literature on ultrastructural lesions in canine CIE and human IBD and offers future direcLons for the study of ultrastructural mucosal lesions in canine CIE. Such lesions might have a higher sensiLvity of detecLon than structural changes revealed upon light microscopy and may even precede or remain afer the reso-luLon of clinical signs and histologic lesions.